ISLAMIC VALUES IN LOCAL CULTURE OF TENGGER TRIBE KANDANGSARI HAMLET MOROREJO VILLAGE PASURUAN REGENCY - Askhabul Kirom (International Journal Education Multicultural of Islamic Society, 2021)
Islamic values are the main basis for shaping the development of society. Islamic values that are emphasized are universal values that are accepted and in accordance with the people of Kandangsari Hamlet, Mororejo Village, Pasuruan Regency. Islamic values aim to form a society that is proud, has a strong identity and is respected by other societies; fostering a happy society; eliminating negative attitudes; and produce quality services. As for the Islamic values that exist in the local culture of the Tengger Tribe, Kandangsari Hamlet, Mororejo Village, Pasuruan Regency, they are harmony, an attitude of shame in a positive sense, sacrifice, mutual cooperation, discipline, tolerance, hope, please help, always grateful, togetherness.Keywords:  Islamic Values, Local Culture, Tengger TribeIslamic values are the main basis for shaping the development of society. Islamic values that are emphasized are universal values that are accepted and in accordance with the people of Kandangsari Hamlet, Mororejo Village, Pasuruan Regency. Islamic values aim to form a society that is proud, has a strong identity and is respected by other societies; fostering a happy society; eliminating negative attitudes; and produce quality services. As for the Islamic values that exist in the local culture of the Tengger Tribe, Kandangsari Hamlet, Mororejo Village, Pasuruan Regency, they are harmony, an attitude of shame in a positive sense, sacrifice, mutual cooperation, discipline, tolerance, hope, please help, always grateful, togetherness.